Protocol for the generation and immunostaining of thick murine lung tissue slices - Ali Khadim; Mahtab Shahriari Felordi; Hawlader Sabbir Hasan; Georgios Kiliaris; Mahsa Zabihi; Hannah Hofmann; Elie El Agha (STAR Protocols)
Summary: Precision-cut lung slices (PCLSs) largely preserve the native structural and cellular complexity of the lung, enabling detailed spatial analysis of resident cell populations. Here, we present a protocol for generating PCLSs from mouse lungs for subsequent immunofluorescent staining to detect protein expression. We describe steps for preparing animals and instruments and generating PCLSs. We then detail procedures for immunofluorescence for ACTA2 while preserving the endogenous fluorescent reporter in PCLSs and co-staining ACTA2 and MKI-67 with the endogenous reporter in PCLSs.For complete details on the use and execution of this protocol, please refer to Khadim et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.